International Collaboration in Medical Research in Latin America and the Caribbean (2003-2007) - Chinchilla-Rodríguez, Zaida (2012)
Bibliometric techniques and social network analysis are used to define the patterns of international medical research in Latin America and the Caribbean based on information available in the Scopus database. The objective was to ascertain countries' capacity to establish intra- and extraregional scientific collaboration. The results show that increased output and citations in medical research have heightened the region's presence and participation in the international scientific arena. These findings may be partly influenced by the inclusion of new journals in the database and regional initiatives that may have enhanced collaboration and knowledge transfer in science. The overall rise in partnering rates is slightly greater intra- than extraregionally. The possible effect of geographic, idiomatic, and cultural proximity is likewise identified. The "scientific dependence" of smallor developing countries would explain their high collaboration rates and impact. The evidence shows that the most productive countries draw from knowledge generated domestically or by their neighbors, which would explain why impact is so highly concentrated in the regions with the greatest output. The need to incentivize intraregional relationships must be stressed, although international initiatives should also be supported